CT Findings and Clinical Features as Markers for Patient Outcome in Primary Pontine Hemorrhage - Wessels, Tiemo; Möller-Hartmann, Walter; Noth, Johannes; Klötzsch, Christof (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: The overall mortality rate of primary pontine hemorrhage (PPH) in recent studies is 40–50%. The aim of the present study was to analyze the predictive value of clinical and neuroradiologic parameters concerning the outcome of patients with PPH.METHODS: We reviewed the clinical data of 29 consecutive patients (mean age, 59 ± 13.5 years; 12 women, 17 men) with PPH. National Institutes of Health Stroke Scale (NIHSS) and Glasgow Coma Scale (GCS) scores were assessed on admission, and NIHSS, GCS, and Glasgow Outcome Scale (GOS) scores were assessed on discharge. The hemorrhage volume was calculated by using a previously published formula. Clinical manifestations, outcome, and volume and location of the bleeding were correlated.RESULTS: The mean GCS score on admission was 6.8 ± 3.9 and increased to 9.0 ± 3.9 on discharge. The NIHSS score improved from 29.1 ± 12.5 to 12.1 ± 7.3. Nine patients (31%) died as a result of PPH after 5 ± 3 days. The mean GOS score was 3.0 ± 1.5 (3.9 ± 0.8 for patients who survived). Arterial hypertension was the most common risk factor (90%); other causes were anticoagulation therapy (7%) and amyloid angiopathy (3%). A high correlation was observed between a poor outcome (GOS score < 4) and hematoma volume greater than 4 mL (P = .006), ventral hemorrhage (P < .001), and necessity for mechanical ventilation (P < .001). Patients with dorsally located hematomas less than 4 mL in volume had a significantly better outcome.CONCLUSION: The prognosis of PPH is better than commonly expected. Most patients with moderate neurologic deficits on admission and dorsally located small hematomas are able to survive PPH with minor neurologic deficits.